An exploratory survey on community pharmacists' service provision for pregnant and lactating women in Sharjah, United Arab Emirates. - Zahraa Abdullatif Akkad; Muaed Alomar; Subish Palaian (PLoS ONE, 2022)
Over-the-counter (OTC) medications are generally deemed safe to be used during pregnancy and lactation. However, some products can be harmful to the mother, fetus or breast-fed child, which presents a challenge to health professionals and consumers. This study was aimed at assessing the practice of OTC medication dispensing and counseling services provided to pregnant and lactating by community pharmacists (CPs). A cross-sectional descriptive questionnaire-based survey was answered during February-November 2020, by licensed CPs practicing in Sharjah, United Arab Emirates. The determination of the significant factors associated with the CPs' views and OTC medication dispensing during pregnancy and breastfeeding was carried out using logistic regression. Among 256 respondents, dispensing medicines and referral to a physician were the predominant services provided to pregnant and lactating women. Respondents dispensed medications mostly to treat headache (74.2%), fever (62.5%) in pregnant women, and headache (81.3%) and fever (65.2%) in lactating mothers. Referral to a physician was common in pregnant women in the following cases: varicose veins (72.7%), swelling of the feet and legs (71.9%), and vaginal itching (53.9%). In breastfeeding women, the referrals were commonly for varicose veins (79.7%), swelling of the feet and legs (73.0%) and mastitis (70.3%). Most participants came to an agreement that CPs are capable of counselling and providing pregnant and lactating women the best OTC treatment. Around 35% of the respondents stated that OTC medicines are not safe to be used during pregnancy. One in five respondents stated that OTC medicines are not safe for breastfeeding women. CPs were confident to counsel and provide advice to pregnant and breastfeeding women to address medication and health problems. Proper utilization of CPs can contribute largely to the healthcare system in managing common minor ailments in pregnant and lactating women, reducing the need to visit the physician and enhancing patient safety.